Trophoblast expression of fms-like tyrosine kinase 1 is not required for the establishment of the maternal–fetal interface in the mouse placenta - Hirashima, Masanori (National Academy of Sciences, 2003)
Fms-like tyrosine kinase 1 (Flt1)/vascular endothelial growth factor (VEGF) receptor 1, a receptor for VEGF-A and placental growth factor, is expressed in the spongiotrophoblast layer that segregates the maternal and fetal vasculature in the mouse placenta. A soluble form of Flt1 (sFlt1) produced in the mouse and human placenta can also be detected in the maternal blood. Levels of maternal sFlt1 are elevated in preeclampsia, suggesting that placental sFlt1 plays roles in regulating the maternal vasculature during pregnancy. However, it remains to be determined whether placental Flt1/sFlt1 serves as a regulator of VEGF-A activity in the placenta per se. Here, we investigated the placental development in Flt1-deficient mice. Flt1 is expressed in a subpopulation of ectoplacental cone cells and later marks the spongiotrophoblast cells, peri/endovascular trophoblast cells, and trophoblast glycogen cells. The labyrinth of Flt1(lacZ/lacZ) placentae lacked the fetal capillary network because of a defect in allantoic mesoderm invasion. To address whether the absence of Flt1 in the trophoblast alone affects placental development, we investigated chimeric placentae comprised of Flt1(lacZ/lacZ) trophoblast and Flt1(+)(/)(+) mesoderm, generated by tetraploid aggregation. Fetal growth was supported normally, and no defect in the formation of placental circulation into the maternal spiral artery or invasion of peri/endovascular trophoblast was detected. These findings indicate that trophoblast-derived Flt1/sFlt1 is dispensable for the initial establishment of the maternal–fetal interface in the mouse placenta. Targeting maternal sFlt1 levels for treatment of preeclampsia may thus be possible without affecting the proper formation of the placenta.